Human Freedom and the 'Reality of Society': Origins and Development of Karl Polanyi's Ideas during the Interwar Period - Thomasberger, Claus (History of Economic Thought, 2005)
Karl Polanyi's most famous book, The Great Transformation, contains several ideas and theoretical notions which are at the heart of long-lasting controversies throughout the social sciences. Categories such as "double movement," "embeddedness," "disembedding," "market society," or "social freedom" have proved to be fruitful notions not only in anthropology, but also in sociology, political sciences, and economic history. The recent three volume publication of Karl Polanyi's writings during the interwar period–including published articles and unpublished manuscripts–opens for the first time the possibility to have a closer look at the origins and the development of some of Polanyi's concepts during the interwar period. In the paper titled "Human Freedom and the Reality of Society–Origins and Development of Karl Polanyi's Ideas during the Interwar Period," Claus Thomasberger addresses Polanyi's idea of a polar relationship between human freedom and the "reality of society." The paper offers new insights, discussing central questions which are crucial to the understanding of Polanyi's reasoning: Where are the roots of his central categories? What influence did Marx have on Polanyi's thinking? What is the relationship between Polanyi's approach and the Austrian School of Economics? Is it appropriate to read his work in terms of an institutional approach? In order to give an answer to these questions, the paper goes back not only to the 1930s, but to the 1920s as well. As it demonstrates, Polanyi had already developed the core ideas of his thinking in Vienna, participating actively in the discussions between the Austrian School of Economics and Austro-Marxism about the possibilities of a socialist society.
Economics; Philosophy
Keywords: history of economic thought: individuals; reality of society

Massacre of the Doves?: Interpreting Israel's 2003 Elections - McMahon, Sean F. (British Journal of Middle Eastern Studies, 2005)
This article argues that Israel's 2003 elections are best understood as a deeper embedding of neoliberalism in the Israeli polity. It is argued that the most accurate characterization of the elections is as an articulation of Polanyi's Phase I of the double-movement. The argument is developed in four stages. First, the Israeli elections are understood as a local reaction to the multilayered processes of globalization. The Israeli state and its elections are located in the neoliberal ideology which underwrites the phenomenon broadly defined as globalization. Second, the election results are reviewed. Third, the dominant interpretations of the elections are critically examined. Specifically, representations of the elections as a defeat of the parties of peace and as a rebuke of Sephardim/ultra-Orthodox influence in Israeli government are interrogated. Fourth, the coalition negotiations of February 2003, the constitution of Israel's 30 th government and some of the initiatives undertaken by Finance Minister Benjamin Netanyahu are explicated through deployment of Polanyi's double-movement framework.
Political Science; Area Studies
Keywords: Israel - politics and government; double movement; elections; globalization; neoliberalism

Fighting standards with standards: harmonization, rents, and social accountability in certified agrofood networks - Mutersbaugh, Tad (Environment & Planning A, 2005)
In this paper I explore the remaking of globalized standards through harmonization, and its impact upon certified-organic and fair-trade agrofood networks. I focus on certification standards and discuss four shifts associated with globalized standards (an increased importance of multilateral institutions, changes to standards language, displacement of network-specific standards, and a shift away from relational standards). It is then argued, with reference to value-chain rent theory, that the shift to globalized standards has transformed rent relations in ways that benefit certain actors (that is, retailers) and imperil the earnings of others. In brief, globalized standards increase the costs of standards compliance, the full burden of which falls upon immiserated producers, to the point at which farmers see little economic advantage to certified-organic and fair-trade production. I then examine social-accountability standards that seek to `fight standards with standards' by championing the consolidation of strong labor and environmental protections under a single label. The study suggests that a single-label strategy can be successful, yet must struggle to overcome a Polanyian double bind, for, in order to build broad coalitions necessary to extend the reach of protective standards, the coalitions must include corporate interests that prefer weaker, contract-based standards.
Geography
Keywords: agricultural accounting; agricultural industries; applied ecology; environmental policy; retail industry; retail stores

Polanyi, Chayanov, and Lessons for the Study of the Informal Sector - Özveren, Eyüp (Journal of Economic Issues (Association for Evolutionary Economics), 2005)
This article offers an alternative institutional economic approach to the informal sector by interpreting the works of economists Karl Polanyi and Alexander Vasil'evich Chayanov. Far from withering away, the informal sector continues to occupy an important place within economies in general and within the so-called developing economies in particular. Relatively speaking, the informal sector is inferior and more spontaneous, if not actually incomplete. Within the informal sector there are numerous small competitive firms, free entry, market-determined factor and product prices, together with a concentration of petty retail and services, labor-intensive production processes, and low productivity. According to Polanyi, one major drawback of mainstream economics is the insistence that the market mode is synonymous with the economy, and, under the weight of this assumption, formalistic economic analysis is assumed to be universally applicable to the study of all times and places. As a consequence, mainstream economists see markets where there are none.
Economics
Keywords: CHAYANOV; Alexander V.; POLANYI; Karl; 1886-1964; economic sectors; economics; informal sector (economics); labor productivity; labour productivity; small business

The role of the UN Millennium Declaration and of the World Economic and World Social Forum for Structural Change - Abrahamson, Hans (Conference Papers – International Studies Association, 2005)
Globalisation can in a polanyian sense be understood as a double movement. Societal reaction to the shortcomings of the corporate driven process of globalisation from above (the first movement) creates a counter movement from below (the second movement). The relations between different actors within the political landscape and the area of tensions between the two movements are characterised by the gramscian war of position and its power struggle over the hegemonic discourse. At times the constellation of political forces permits an institutionalised state of equilibrium built on converging interests between different social forces. During the Westphalia era with its nation-state project the social contract constituted the base for such an historic compromise. The end of the cold war and strengthened process of corporate globalisation has eroded the base for this social contract on a national level increasing development gaps not only between countries but also within countries. This paper addresses the question of room for manoeuvre for structural change in order to deal with present challenges within the Global Political Economy. It discusses how possibly the UN Millennium Declaration could be used in the ongoing discursive war of position between actors at the World Economic Forum in Davos (representing the first movement) and actors at the World Social Forum in Porto Alegre (representing the second movement) in order create a social base for a new social contract albeit on the global level. Such a discussion also illustrates present potential of these arenas in contributing to a future global political economy of peace and development.
Peace Studies; Development Studies
Keywords: United Nations; World Economic Forum; economics; forums (discussion & debate); globalization; hegemony; political science

Bridging boundaries and Mending Fences? Finding "community" in transboundary conservation approaches - Hoon, Parakh (Conference Papers – International Studies Association, 2005)
The article presents the conference paper titled "Bridging boundaries and Mending Fences? Finding community in transboundary conservation approaches" prepared for the "Annual Convention of the International Studies Association" held in Honolulu, Hawaii. It discusses the implementation of the Community Based Natural Resource Management in Botswana in early 1990s. It examines the contemporary applications of the idea of embeddedness which was coined by intellectual Karl Polanyi as an analytical and ideological foil to the notion of self-regulating markets.
Political Science
Keywords: Botswana; conservation of natural resources; conservation projects; international relations; self-regulating market

Embeddedness as a Process - Chajewski, Leszek (2005)
This article describes a strategy of modeling embeddedness of economic behavior as a process, as opposed to viewing it as a time-independent relationship between behavior and a social factor in which it is subsumed. I first reconstruct Polanyi's classic processual model of embeddedness and derive from it a set of intuitive tests, which are then applied to key modern approaches in economic sociology: structural, neo-institutional, neo-weberian and Fligstein's embeddedness-as-identity-formation approach. Finally, I describe main analytic and empirical consequences of the processual approach to embeddedness. Key among these consequences is that not all forms of embeddedness are of equal significance, therefore, economic sociology's empirical focus should shift from demonstrating that behavior is more likely to be embedded than not, to the forms of economic behavior that are likely to dominate alternative types of behavior.
Sociology
Keywords: cultural and neo-weberian perspectives in economic sociology; economic sectors; economic systems; embeddedness; embeddedness and identity formation; embeddedness process; empirical research; forms of economic integration; market transitions; neo-institutionalism; new economic sociology; social factors; social status; socioeconomics

"Economic Life, Institutions, and Social Action: Reflections on Polanyi's Approach to Studying Economic Life" - Gemici, Kurtulus (2005)
The article focuses on the relevance of economist Karl Polyani's economic theories and tries to analyze if his book titled "The Great Transformation," could be considered as the foundation of current economic sociology and international political economy. The author of the article says that Polayni's theories focuses on contemporary economic sociology, market economy's self-destructive approach and consideration of the market economy as integral part of the society. His work on institutedness and economy's embedness in society are working as base for most of the challenging theories in economic sociology.
Sociology
Keywords: Great Transformation; The (Book); capitalism; economic behavior; economics; embeddedness; institutions; methodology; socioeconomics

Gramsci, Polanyi and Impressions from Africa on the Social Forum Phenomenon - Bond, Patrick (International Journal of Urban and Regional Research, 2005)
The rise of the Social Forum phenomenon has been heartily welcomed, partly so as to unite diverse discourses of anti-neoliberal and anti-imperialist resistance under a common banner. There are debates worth flagging, however, that draw our attention to political philosophies (typically binary statist versus anti-statist disputes), visions of agency (typically networked movements versus parties), and potentials for revolutionary processes to emerge within ‘civil society’. In the spirit of Polanyi, many South Africans and other Africans are working on ‘decommodification’ strategies that range from particular sites of project-level struggles to national, regional and international advocacy. But we must be conscious, as well, of warnings by Gramsci about the long march through a civil society often co-opted to support state and neoliberal projects. The merits of African intellectual engagements with radical social movements have been shown in sites such as South African cities, but the African Social Forum awaits further opportunities to welcome allied researchers and academics. As the World Social Forum comes to Africa in 2007, Marcuse’s hope that the constituent movements begin to coalesce around a program is timely. However, this is likely to emanate more from intra-sectoral networks rather than from multidisciplinary moments such as the WSF itself. La montée du phénomène des Forums sociaux a été accueillie chaleureusement, en partie comme manière d’unifier sous un même drapeau les multiples discours de la résistance anti-néolibérale et anti-impérialiste. Certains débats éminents attirent pourtant l’attention sur des philosophies politiques (généralement des oppositions binaires étatistes/anti-étatistes), des visions de l’intermédiation (en général, mouvements interconnectés/partis) et des processus révolutionnaires susceptibles de naître au sein de ‘la société civile’. Dans l’esprit de Polanyi, nombre d’Africains, du Sud et d’ailleurs, s’emploient à des stratégies de ‘démarchandisation’ couvrant à la fois sites de conflit particuliers liés à un projet et plaidoyers aux niveaux national, régional et international. Toutefois, il ne faut pas oublier les avertissements de Gramsci pour qui la longue marche passant par la société civile risquait d’être cooptée afin de soutenir des projets gouvernementaux ou néolibéraux. Si les engagements d’intellectuels africains aux côtés de mouvement sociaux radiaux se sont révélés bénéfiques dans des cas tels que les villes d’Afrique du Sud, le Forum social africain espère d’autres occasions de rallier chercheurs et universitaires. Comme le Forum social mondial se tiendra en Afrique en 2007, l’espoir de Marcuse — de voir les mouvements constitutifs s’unir progressivement autour d’un programme — est d’actualité. Cependant, cette évolution viendra plus probablement de réseaux intra-sectoriels que d’élans multidisciplinaires comme le FSM.
Geography; Political Economy
Keywords: GRAMSCI; Antonio; 1891-1937; South Africa; decommodification; development studies; geography; social forum phenomenon

From flows to violence - Kalb, Don (Anthropological Theory, 2005)
Recent globalization theory reflected a chain of world historical events since the end of the Cold War. Globalization theories were tools for the making of political alliances between market liberals and political, liberals. From the mid-1990s a broad range of institutionalist social science programs showed that globalization outcomes were often better explained by institutional logics (including cultural ones) than by global flows per se. This is, among others, illustrated by the debate on global inequality data. The emerging debate on empire and imperalism is discussed as a logical offshoot of the globalization discussion just as the phenomenon itself is seen as a likely outcome of an epoch of market-driven globalization. Globalization was predicated on the emergence of a US-led transnational western state structure on behalf of the transnational capitalist class based in finance and the large corporations. Territory and space have become more important rather than less, but the explanation of regional trajectories must now be located more firmly in the interaction between local and global structures. This leads to a new agenda in the social sciences: one oriented toward common interdisciplinary programs with a limited range of core questions - about state formations, class formations, mobilizations, claim making, and associated cultural processes. Programs should be more theory driven, comparative, and in search of explanations of divergent spatial and temporal outcomes of universal process.
Anthropology
Keywords: alliances (international relations); civilization; cultural policy; dual polarization; empire; globalisation; globalization; imperialism; international relations; social sciences & state; transnational capitalist class

Beyond Boganism - Brown, Beth; Brown, Doug (Journal of Popular Culture, 2005)
The article analyzes the global economy by subjecting it to an interpretive scheme derived from popular culture Boganism, an Australian colloquialism or street slang used by teenagers. Boganism, the social phenomenon of being both unaware and irresponsible, is the result of a particular type of human abandonment. This abandonment is linked to the new hypercapitalism of globalization. The article will establish the structural roots of boganism, examine the case of the abandonment of U.S. youth, and conclude with reform recommendations necessary to shift us beyond boganism to a culture of sustainability. Karl Polanyi, a Hungarian economist, argued a half century ago that the birth of capitalism meant the emergence of what he called the disembedded economy. Polanyi's essential problem with capitalism, when it emerged in the sixteenth century, was that it creates a society in which everyone is dependent on markets to meet their basic needs. The pace of life has clearly increased with the maturation of capitalism and industrialism. But with the high-technology revolution, accompanied as it has been by the globalization of capitalism, what is happening is acceleration of everyday life, the economy, market transactions, and much more. Stratification: relationships of supra- and subordination, relations of domination and injustice. These are the social dimensions and institutional, structural relations between people and groups that have played defining roles in social, political, and economic analysis over the last three centuries of industrialism. Categories of stratification include classism, racism, statism, and sexism, and others. Along with these, we can add boganism.
Political Science; Economics
Keywords: capitalism; disembedded economy; disembeddedness; globalization; popular culture; socioeconomics

Labour and Globalization: Towards a New Internationalism? - Ramasamy, P. (Travail et Mondialisation: Vers un nouvel internationalisme?, 2005)
A one-dimensional view of capitalism inevitably leads to the conclusion that labour is in a state of deep crisis. However, if we examine globalization as a contradictory process, then it is possible to regard its relationship with labour as a transformative one. In this context, the decline of trade union density in developed countries and the rise of new forms of trade unionism in selected countries of the South, illustrate the contradictory relationship between labour and capital. In accordance with Marx, capitalist expansion not only does away with old forms of labour organizations, but has the tendency to create new forms of labour resistance. Similarly, Polanyi argues that attempts to disembed the economy (return to free market enterprise) from the rest of society will be resisted by societal forces. (English)
Political Science
Keywords: capitalism; developed countries; embeddedness; free enterprise; globalization; international trade; labor; labor unions; labour; labour unions; political doctrines

Economics and the Space of Modernity: - Escobar, Arturo (Cultural Studies, 2005)
This text was the original second chapter of the author's doctoral dissertation (Escobar 1987); this chapter was never included in the book that eventually grew from the dissertation (Escobar 1995). Although the chapter's contribution to debates on the economy are largely synthetic and certainly not original, the author wanted to publish it for a number of reasons. First, the alleged triumph of neo-liberal ideologies and the increase in depth and scope of market cultures at present make even more important the task of cultural analysis of economics and the economy. This paper was an effort in this direction, particularly to mapping the genealogies of what in the paper is called ‘the Western economy’. Second, there have been some recent claims that the cultural analysis of economics and the economy has hardly been broached. References to Polanyi's foundational role in this respect are, of course, de rigueur, but one only needs to point at the pioneering work of Stephen Gudeman since the 1980s to dispute this claim. Third, the same cultural analysis is experiencing a much needed surge, with several groups today fully engaged with it from various – some times overlapping – perspectives. Finally, the impetus for this piece also comes from the creative efforts by a number of social movements in the world – such as some of the autonomistas in Argentina – to go even beyond ‘rethinking’ the economy to propose that what is needed is a new invention altogether.
Anthropology; Cultural Studies
Keywords: anthropology of modernity; cultural studies; cultures of economy; economic history; economics; genealogy; modernity; resistance; social history; third world

The fruits of intellectual production: economic and scientific specialisation among OECD countries - Laursen, Keld; Salter, Ammon (Cambridge Journal of Economics, 2005)
This paper brings together data from 17 OECD countries on scientific publications, patents and production, to explore the relationship between scientific and economic specialisation for 17 manufacturing industries. Since Marx, there has been a fundamental debate in economics about the link between science and the economic system. Marx argued that the needs of production shape scientific developments and that science has become a factor of production, whereas Polanyi argued that developments in science are largely independent of the economic sphere. Using a panel data model and econometric estimations at the industry level, the paper derives some hypotheses from the two positions and finds that, while the overall evidence on the link between national production and scientific specialisation is mixed, it is important to have high levels of relevant to-the-industry scientific strength per capita in order to be specialised in science-based industries.
Economics
Keywords: bibliometric data; econometrics; industries; international economic specialisation; manufactures; manufacturing industries; patent laws & legislation; patent suits; science & industry; scientific specialisation

The Global Resistance Reader - Amoore, Louise (Psychology Press, 2005)
The Global Resistance Reader provides the first comprehensive collection of work on the phenomenal rise of transnational social movements and resistance politics: from the visible struggles against the financial, economic and political authority of large international organizations such as the World Trade Organization, World Bank and International Monetary Fund, to the much less visible acts of resistance in everyday life. The conceptual debates, substantive themes and case studies have been selected to open up the idea of global resistance to interrogation and discussion by students and to provide a one-stop orientation for researchers, journalists, policymakers and activists.
Geography; Political Science
Keywords: GILL; Stephen; political science / globalization; political science / reference

Engendering Charismatic Economies: Pentecostalism, Global Political Economy, and the Crisis of Social Reproduction - Barker, Isabelle V. (Conference Papers – American Political Science Association, 2005)
Pentecostalism is the fastest growing religion in the world today. A number of explanatory theories exist, but in this paper, I hone in on the nexus between economic restructuring and Pentecostalism to explore this extraordinary expansion. Bringing together the work of feminist political economists and of Karl Polanyi, I argue that neo-liberal globalization threatens mechanisms for meeting social reproductive needs. Neo-liberalism cannot meet these needs on its own, and I suggest that Pentecostalism addresses these gaps, effectively embedding neo-liberal economic policies. It does so by facilitating norms and practices on the part of individual adherents to provide for the care work required for human reproduction; to adopt norms required of a neo-liberal labor force; and, to embrace the kind of transnational social identity that is compatible with labor migration and global markets. ..PAT.-Conference Proceeding
Political Science
Keywords: CHRISTIANITY; GLOBALIZATION; Globalization; PENTECOSTALISM; Pentecostalism; Polanyi; Karl; 1886-1964; RELIGION & sociology; feminism; feminist political economy; neo-liberalism; social reproduction

Citizenship unbound: The global politics of neo-liberalism and labor migration - Barker, Isabelle Virginie; Cornell, Drucilla (2005)
This dissertation considers the status of citizenship in an era of neo-liberal globalization. Citing increased labor migration and the retreat of domestic social policies throughout the world as intersecting processes, I argue that narratives of national citizenship lie at the heart of this intersection, transformed by rapidly changing geopolitical conditions. Despite challenges, national citizenship remains a relevant political category, though reformulated along the lines of neo-liberal principles of privatization, market rationality, and individual responsibility. the politics and rhetoric surrounding the 1996 federal reforms of immigration and social policy in the United States serve as one example of this process. I further support my claim with an extensive illustration of the linkages between the restructuring of U.S. health care policy for senior citizens with the increased migration of women from the global South to provide low-wage direct care services for the aging population in the United States. I then evaluate the work of Martha Nussbaum, Amartya Sen and Thomas Pogge, arguing that their respective efforts fail to offer effective interventions into the fate of democratic citizenship in an era defined by expanding inequalities and shrinking public spaces. I conclude by bringing together the works of Karl Polanyi, David Held, and Hannah Arendt with feminist scholarship to develop a feminist theory of democracy and political membership for the twenty-first century. (Copyright applies to all Abstracts.)
Political Science
Keywords: ARENDT; Hannah; HELD; David; NUSSBAUM; Martha; POGGE; Thomas; SEN; Amartya; citizenship; feminist theory; globalization; labour migration; political science; women's studies

José Bové and the Globalisation Countermovement in France and Beyond: A Polanyian Interpretation - Birchfield, Vicki (Review of International Studies, 2005)
This article illustrates the continuing salience of Karl Polanyi's The Great Transformation (1944) by employing two of its central concepts, fictitious commodities and the double movement to interpret the globalisation countermovement and one of its most important figures, José Bové. I explain the transformation of José Bové from rural sheep farmer to French folk hero and global activist and analyse the extent to which his rhetoric and political actions are congruent with Polanyi's key insights. Arguing against the media characterisation of Bové as protectionist, I show that this misrepresentation conceals the larger ideological threat his movement poses to institutionalised politics and neoliberal hegemony. The political vision underlying Bové's symbolic media tactics and articulated in his book, Le Monde n'est pas une Marchandise, reveals significant manifestations of Polanyi's chief intellectual legacy - an unparalleled critique of economism and market society. An often neglected question in Polanyian scholarship is whether or not it is possible to have a market economy without becoming a market society. A more careful analysis of Polanyi's thought sheds light on this key issue while the empirical analysis of Bové's movement reveals its implications for French society and the broader globalisation countermovement.
Political Science
Keywords: capitalism; commodities; countermovement; economic globalization; economic liberalism; free market economies; globalization; international economics; political movements; social movements

Two heterodox economists: Neurath and Karl Polanyi - Giandomenica, Becchio (MyScienceWork Working paper No. 11/2005 Università di Torino 1, 2005)
This paper is based on the idea that between the 1920s and the mid-1930s in Vienna there were two forms of heterodox economic theory: the Austrian economic school headed by Ludwig von Mises and another interesting form of heterodox economics opposed to the Austrian school (above all politically) and pursued by various social thinkers (Otto Neurath, Karl Polanyi, Otto Bauer, Felix Schaffer, Felix Weil, Jacob Marschak). They were engaged in the debate on the possibilities of a planned economy: Austrian socialist economists proposed a sort of ‘third’ way between pure capitalism (whose Viennese stronghold was the Austrian economic school) and orthodox communism à la Kautzsky (deeply rooted in Germany). This paper focuses on the affinities between Neurath and Polanyi’s economic thought: despite some major differences between them, they shared a common philosophical background on which they founded their heterodox economic theory. After a brief historical premise, there is a first part, which deals with the debate on a planned economy and a second part, which deals with the influence of Neurath on the Polanyi’s vision of the faults of the neoclassical economic theory: the concepts of “disembedded economy” and of the so-called “economicistic fallacy”. NEURATH AND POLANYI IN VIENNA Neurath described himself as a ‘social engin
Economics; Philosophy
Keywords: Austrian economic school; NEURATH; Otto; economics; heterodox economics; philosophy; political science

A New Middle East? Globalization, Peace and the Double Movement - Guy Ben-Porat (International Relations, 2005)
The rise and fall of the New Middle East (NME) cannot be separated from wider global developments and must therefore be studied in relation to them, in both their ideational and material aspects. The ideological background of the NME has drawn upon the ideology of globalization and shares its underlying tenets of rationality, professionalism and virtues of market economy. In the early 1990s a discourse of globalization was set in motion, highlighting economic and technological development that supposedly rendered territory and territorial disputes marginal or irrelevant. The NME, supported by Israel's business, political and academic elites, advocated liberal economics and peace as a solution to the region's problems. But Israeli elites have failed to turn the idea of the NME into a hegemonic concept, as this attempted liberal hegemony invoked a Polanyian double movement that undermined the peace process. The scenario of the NME and the trade-off between territorial integrity and promised regional prosperity not only met fierce ideological rejection, but, perhaps more importantly, failed to persuade the many more skeptics. Limited in its appeal and lacking sufficient legitimacy, the peace process was exposed to derailment by extremists, locking the region into cycles of violence.
Political Science; International Relations
Keywords: Middle East; capitalism; double movement; economic development; globalization; ideology; international relations

Karl Polanyi - Isaac, Barry L. (Edward Elgar Publishing, 2005)
This unique Handbook contains substantial and invaluable summary discussions of work on economic processes and issues, and on the relationship between economic and non-economic areas of life. Furthermore it describes conceptual orientations that are important among economic anthropologists, and presents summaries of key issues in the anthropological study of economic life in different regions of the world. Its scope and accessibility make it useful both to those who are interested in a particular topic and to those who want to see the breadth and fruitfulness of an anthropological study of economics.
Anthropology
Keywords: economic anthropology; economics and finance; social policy and sociology

The Economy as a Polity: The Political Constitution of Contemporary Capitalism - Joerges, Christian; Stråth, Bo; Wagner, Peter (Psychology Press, 2005)
The debate about so-called economic globalization has reached a new phase. The hegemony of neo-liberal thinking has ended, in the face of both the increased and increasingly effective resistance to the social consequences of neo-liberal market-making - rising inequality and insecurity throughout the world - and the visibly dysfunctional effects of lack of regulation - currency and stock market crashes, among others. Thus, the story about 'the rise and fall of market society', which was first told in these terms by Karl Polanyi sixty years ago, is about to receive a new chapter. In this light, this volume offers a novel perspective on the interaction between states and markets. In contrast to much of current theoretical wisdom, we hold, with Polanyi, that markets cannot even be consistently thought of as self-regulating. Markets are always constituted by framework conditions that cannot be set by the markets themselves. The range and scope of market rules requires some agreement, or at least acceptance, for economic exchange to be working at all; in democratic societies, these rules are at least theoretically always subject to political debate and decision. To put the issue in theoretical terms: even the most pure version of economic liberalism always entails at the same time a political philosophy. This volume, thus, proposes to understand contemporary capitalism by regarding the economy as a polity, as an arrangement that is always constituted by some collective agreements about its mode of operation. Such theoretical position on its own, though, is insufficient to explain the workings of capitalism once and for all. Historical experiences with capitalism have led to transformations that require new angles of analysis. It is in the nature of the struggles over the embedding of markets that their outcomes are subject to historical contingency and cannot be completely known beforehand. Beyond a review of the theoretical tools at hand, therefore, the analysis of the contemporary constellation of capitalism, also requires an understanding of its recent transformations. This is the second task to which this volume is devoted - through analyses of the current state of regulation of labour and money and through investigations of the historical development and novel forms of the mode of embedding markets. While focusing on the renewal of the analysis of contemporary capitalism, the volume also points to fruitful directions of institutional or policy change and provides perspectives for a much-needed political renewal, with a particular focus on the European Union as a novel polity embedding the European economy.
Political Science; Economics
Keywords: business & economics; economic policy; free enterprise; public policy

Globalization - McMichael, Phillip (The Handbook of Political Sociology states, civil societies, and globalization, 2005)
Philip McMichael casts a critical eye on the process of globalization suggesting that it takes different forms across time and space. He specifies contemporary globalization as a discursive project, geared to institutionalizing corporate markets through multilateral and regional economic agreements driven by powerful states. From this perspective of depicting globalization as an exercise in power, he examines political countermovements to globalization. Global justice movements, he argues, are globalization’s “historical and relational barometer,” and they operate at various, but often interrelated, scales. Work- ing from Karl Polanyi’s “double movement” of implementation of and resistance to economic liberalism, McMichael questions the adequacy of Polanyi’s formulation for the elaboration of market rule in the twenty-first century. This question concerns the conventional interpretation of “sovereignty” as the centerpiece of nation-state formation, including the development of citizenship. Here, globalization is viewed through the lens of a sovereignty crisis, where corporate market rule compromises the social contract upon which the state/citizen relation is founded. The crisis is expressed differently across the world, as the impact of market rule generates alternative social movement conceptions of sovereignty, especially in the global south where corporate globalization is realized through a drastic intensification of social exclusion.
Sociology
Keywords: counter-movement; critique; double movement; globalization; political sociology

Ancient Athens & modern ideology: value, theory & evidence in historical sciences : Max Weber, Karl Polanyi & Moses Finley - Nafissi, Mohammad (Institute of Classical Studies, School of Advanced Study, University of London, 2005)
History; Classical Studies
Keywords: Athens (Greece); WEBER; Max; 1864-1920; civilization; classical civilization; classical philology; economic theory; economics; history / ancient / Greece; social science / sociology / general

What Can Marxists Learn From Polanyi? - Özel, Hüseyin; Yılmaz, Erdal (2005)
The starting point of this paper is this comment by Rhoda Halperin on the relationship between Marx and Polanyi. Our objective is, however, to examine how reading of Polanyi could be useful to understand, or supplement, Marx’s own views on both capitalism and the “human condition” in general, rather than vice versa. In this regard, we argue first that those followers of Polanyi who believe that Marx should be treated as a rival of Polanyi, and that Marx’s “historical materialism” and his critique of capitalism is economically (or technologically) determinist, mechanistic, and reductionist, either misunderstand or misrepresent Marx.. We believe that these properties should be taken as representing the position that could be called as “vulgar” Marxism, rather than representing Marx’s own position. This type of “vulgar” Marxism is first of all positivistic or scientistic in its outlook; that is, it maintains the positivistic distinction between facts and values and thus considers ethics as being trivial in understanding and resisting capitalism. Secondly, its “materialistic conception of history” is guilty of the “economistic fallacy”, since it overlooks the fact only under capitalism do we have an “economic society”. Third, its class conception is mechanistic and reductionistic in that every act of resistance to capitalism must be explained in terms of, and carried out through, class struggle. Last, but not least, the “vulgar” Marxism is fatalistic in the sense that it maintains the view that capitalism will inevitably be collapsed through class struggle. We believe that none of these charges can be sustained if one considers Marx’s work in its entirety, and that there are important affinities and overlaps between Marx and Polanyi.
Economics
Keywords: MARX; Karl; 1818-1883; critique of capitalism; fictitious commodities; substantiveness

Karl Polanyi as a Development Economist - Polanyi Levitt, Kari (Pioneers of Development Economics: Great Economists on Development, 2005)
The history of modern economic thought has been pre-occupied with the question of economic transformation or development. This survey of important contributions to the economics of development includes many economists not normally considered as pioneers in this field. The contributors point to the role of imperialist considerations in the early development of economic thought and the development discourse, and the impact of pressures for social and political reform. The economists and thinkers discussed include William Petty, David Ricardo, Friedrich List, Alexander Hamilton, Karl Marx, Vladimir Ilyich Lenin, Alfred Marshall, Michal Kalecki, John Maynard Keynes, Nicholas Kaldor, Karl Polanyi, Raul Prebisch, Arthur Lewis, Alexander Gerschenkeron and Hans Singe
Economics
Keywords: development economics; economic history

What We Need to Know About the Social Economy A Guide for Policy Research - PRI Project (Government of Canada, 2005)
This guide provides background on the social economy, identifies research issues whose examination would support the development of policies and programs, provides suggestions for how this research might be conducted, and points to some useful information sources. KM: Gov't commissioned - New Approaches for Addressing Poverty and Exclusion
N/A
Keywords: Canada; borderline; government of canada; grey literature; social economy

Surviving Capitalism: How We Learned to Live with the Market and Remained Almost Human - Ringmar, Erik (Anthem Press, 2005)
Human life cannot be reduced to market transactions and human beings cannot only be treated as economic actors. When the power of the market increases, human beings will always try to protect themselves. Given the differences that exist in social and cultural traditions, these protective responses are likely to differ from one society to the other. This is why, even in a global market, diversity is always likely to persist. This book investigates the question of economic globalization - whether it is likely to lead to full convergence between political models and ways of life, or whether, even in a completely globalized world economy, there is likely to be scope for alternative solutions. But in a fully globalized world, how will we survive capitalism?
Political Science
Keywords: economic globalization; globalization

The Transition between the Old and New Traditional Economies in India - Rosser, J. Barkley; Rosser, Marina V. (Comparative Economic Studies (Palgrave), 2005)
We extend Karl Polanyi's traditional economy concept to modern economies with advanced technology that are embedded in a traditional socio-cultural framework. This is the New Traditional economy, seen in parts of the Islamic world and with the Hindu nationalist movement in India. However, rural India is also the largest repository of the Old Traditional economy with its Hindu caste and jajmani system of reciprocal labour relations. The changes in India's complexly mixed economy, with its increasing market and strong planned elements, constitute a transition from the Old to the New Traditional economy. We shall consider this transition both ideologically and systemically.
Economics
Keywords: Hinduism; India; caste; economics; labor; labour; markets; nationalism; new traditional economy; old traditional economy; transition

Social Embeddedness. Within Political Economy: The Work of Karl Polanyi - Watson, Matthew (Foundations of International Political Economy, 2005)
BOOK ABSTRACT: Despite a burgeoning debate on substantive issues in IPE, little attention has been devoted to its theoretical foundations. In this important new text, Matthew Watson reviews the main current theoretical approaches to IPE and highlights the problems that arise from treating 'states' and 'markets' as separate and contesting units of analysis. Foremost among these problems is the lack of attention given to theorizing the constitution of the individual as both an economic agent and a moral being.
Political Science
Keywords: international political economy; social embeddedness